2016
DOI: 10.14260/jemds/2016/812
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dexamethasone and Potassium Chloride as Additives to Local Anaesthetic in Supraclavicular Brachial Plexus Block: A Randomised Controlled Study

Abstract: BACKGROUND AND AIMSSupraclavicular brachial plexus block is ideal for upper limb surgical procedures. Dexamethasone and potassium chloride have been used as adjuncts to prolong analgesia. We aimed to compare the effects of addition of dexamethasone or potassium chloride to local anaesthetic solution of bupivacaine and lignocaine on the onset time of sensory and motor blockade and duration of blockade in supraclavicular brachial plexus block in patients undergoing upper extremity surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The full‐text manuscripts of the remaining 312 studies were assessed. After including studies from hand searches and revision of search, we identified a total of 100 studies for inclusion in this network meta‐analysis [32–131]. The study flow chart is in online Supporting Information Figure S1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The full‐text manuscripts of the remaining 312 studies were assessed. After including studies from hand searches and revision of search, we identified a total of 100 studies for inclusion in this network meta‐analysis [32–131]. The study flow chart is in online Supporting Information Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐eight articles were peer‐reviewed and indexed trials [32, 34, 36–38, 42, 44, 53, 54, 58, 59, 63, 66, 69, 72, 75, 79, 81–84, 94, 96, 99, 102, 105, 107, 109, 110, 113–116, 123, 124, 127–129], while 62 articles were peer‐reviewed, non‐indexed publications [33, 35, 39–41, 43, 45–52, 55–57, 60–62, 64, 65, 67, 68, 70, 73, 74, 76–78, 80, 83, 85–93, 95, 97, 98, 100, 101, 103, 104, 106, 108, 111, 112, 117–122, 125, 126, 130, 131]. Fifty‐four trials used bupivacaine as their long‐acting local anaesthetic [32–35, 38, 40–44, 46–48, 50, 51, 54, 55, 57–59, 61, 62, 64–66, 68–72, 76, 77, 79, 85, 89–91, 93, 94, 98–101, 103, 104, 106, 112, 116–118, 122, 124–126], 14 used levobupivacaine [37, 45, 63, 73, 78, 82, 83, 86, 87, 97, 109, 111, 115, 121] and 32 used ropivacaine […”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 161 studies, patients received a supraclavicular brachial plexus block, 26,29–160 in 40 studies, patients received an axillary brachial plexus block, 24,27,161–198 in 28 studies, an interscalene block was performed, 25,199–220 in 11 studies, patients received an infraclavicular brachial plexus block, 221–231 one study used a coracoid approach to brachial plexus block 232 and one study used a suprascapular combined with axillary nerve block 233 . A detailed description of included studies is presented in the supplemental content (supplemental table 3, http://links.lww.com/EJA/A839).…”
Section: Resultsmentioning
confidence: 99%